Selective area growth of AlGaN nanopyramids by conventional and pulsed MOVPE. (15th February 2021) - Boughaleb, Sofia; Martin, Brigitte; Matei, Constantin; Templier, Roselyne; Borowik, Łukasz; Rochat, Nevine; Gil, Bernard; Dussaigne, Amélie
Abstract: Planar UV-C light emitting diodes still suffer from low efficiency, mainly due to substrate crystalline quality, p doped conductivity and extraction efficiency. One possible way to overcome partly these issues is to realize the whole UV structure on AlGaN pyramids by selective area growth in order to benefit from the advantages of such structures, i.e. the dislocation filtering and the semi polar planes. We present here a detailed study about the epitaxy of AlGaN nano-sized pyramids by metal organic vapor phase epitaxy on patterned templates presenting different holes apertures and pitches as 1.5 μ m and 4 μ m or 100 nm and 250 nm respectively. While increasing the Al content, their height decreases while the thickness of the deposition on the mask increases whatever the design of the mask. Those changes of the pyramid shapes and deposition are directly linked to the properties of Al adatoms, i.e. low Al diffusion length. Using the conventional growth mode for the epitaxy of those pyramids did not permit the incorporation of Al from the base of the pyramids to their truncated apex. Its presence was concentrated on the edges and top of the pyramids. On the contrary, a pulsed growth mode, coupled with a strongly reduced pitch, allowed an incorporation of Al since the base of the nanopyramid, and a decrease of the deposition height on the mask. These results can be explained by the desorption of Ga species, due to the presence of H2 in the reactor chamber during the step without the metal precursors, leading to a higher Al/Ga ratio. It is even enhanced inside the holes by the reduced pitch.